Limited Adoption of Advanced BIM Tools in Architectural Education: Evidence from Southwestern Nigeria - Orola, B. A.; Uzoagwa, A. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
This study examined the availability and utilization of Building Information Modelling (BIM) tools among architectural educators in three public universities in southwestern Nigeria. Using a purposive sampling technique, a structured questionnaire was distributed to 80 architectural educators, out of which 41 valid responses were received, yielding a response rate of 51%. The survey collected data on the BIM tools accessible to educators, the specific categories of BIM tools they used, and the frequency of such use in teaching and research activities. Findings revealed substantial variability in BIM tool usage across the institutions. 3D Modelling and Rendering & Visualization were used most frequently, while advanced tools linked to multi-disciplinary collaboration, such as MEP Systems Design, Clash Detection, Construction Simulation (4D), and Cost Estimation (5D), were rarely utilized. This pattern indicates that although foundational BIM capabilities are present, higher-level, interoperability-driven tools remain under integrated in architectural education within the selected universities. The study concludes that BIM utilization is uneven and generally limited to basic functions, underscoring the need for more comprehensive integration of advanced BIM tools in architectural curricula in southwestern Nigeria.